Value of Scatter-Graphs for the Assessment of ECG Computer Measurement Results - Morlet, D.; Rubel, P.; Willems, J. L. (Methods of Information in Medicine, 1990)
A new method is presented, different from usual methods, for the discussion of the results of computer ECG measurement programs, based on a new graphical evaluation method. The proposed “scatter-graphs” both highlight the main program results and facilitate the comparison between various wave-recognition algorithms. They allow the distinction between the reliability of an algorithm, which is its capacity to provide a maximum of measurements with a minimum amount of errors, and its precision, i.e., the standard deviation of the differences between its point estimates and the reference.The method proves to be a powerful tool for the discussion of individual, as well as the median program results in CSE Measurement Study. It allows to highlight limitations induced in performance assessment by the variability of the reference itself, and to state that the median program is at least as close to the “Gold Standard” as the median of the referees.
Keywords: ECG Processing; Quantitative Electrocardiography; Program Evaluation; Graphical Evaluation Method; Algorithm Evaluation